Four-week heat acclimation lowers carbohydrate oxidation of trained runners during submaximal exercise in the heat - Xu, Yixiao; Ye, Chengjie; Ma, Su; Gao, Binghong (Frontiers in Physiology, 2025)
PurposeThis study examined the effect of 4 weeks of heat acclimation (HA, 39°C ≤ target Tc < 40°C) on aerobic capacity in middle-and-long distance runners, with a focus on metabolic adaptation.MethodsEighteen male middle- and long-distance runners were randomized into exercise group (C group, n = 9) or heat acclimation group (HA, n = 9). The runners in the C group performed regular exercise training in a thermoneutral environment (20°C < wet bulb globe temperature ≤25°C), whereas the runners in the HA group underwent four-week heat acclimation (39°C ≤ target coer temperature <40°C), 5 days a week, once a day, for a total of 20 sessions over 4 weeks.ResultsAfter 4 weeks of interventions, the core temperature after incremental treadmill test in the HA group (38.2°C ± 0.1°C vs. 38.6°C ± 0.1°C, p = 0.045) was significantly lower than that in the C group. The 4-week HA decreased the 0.4°C core temperature. The VO2 (44.7 ± 1.6 vs. 43 ± 2.9 mL/min/kg, p = 0.008) and velocity (12.9 ± 0.7 vs. 12.4 ± 0.9 km/h, p = 0.02) at the first ventilation threshold and the VO2 (55.9 ± 2.3 vs. 53.9 ± 3.1 mL/min/kg, p = 0.03) at second ventilation threshold increased compared with those in the C group. The carbohydrate oxidation (2.5 ± 0.1 vs. 3.1 ± 0.2 g/min, p = 0.01) at 75% V̇O2max and 85% V̇O2max exercise (3.4 ± 0.1 vs. 4 ± 0.2 g/min, p = 0.02) in the HA group decreased compared with that in the C group.ConclusionFour-week heat acclimation reduced carbohydrate oxidation during submaximal exercise in the heat, indicating improved muscle glycogen utilization efficiency, which supports the enhancement of ventilatory thresholds and thermoregulatory adaptation, thereby improving aerobic capacity in the heat.